Antiangiogenic effects of a novel synthetic curcumin analogue in pancreatic cancer. Issue 2 (28th February 2015) - Nagaraju, Ganji Purnachandra; Zhu, Shijun; Ko, Jasmine E.; Ashritha, Nakkana; Kandimalla, Ramesh; Snyder, James P.; Shoji, Mamoru; El-Rayes, Bassel F.
Highlights: Curcumin analogues UBS109 and EF31 with improved solubility have been developed. UBS109 and EF31 have increased antiangiogenic effects on PC in vitro and in vivo . UBS109 and EF31 inhibited NF-κB, HIF-1α and HSP90 leading to decreased angiogenesis. UBS109 and EF31 are promising new drugs with effects on angiogenesis in PC. Abstract: Hypoxia-inducible factors (HIFs) and NF-κB play essential roles in cancer cell growth and metastasis by promoting angiogenesis. Heat shock protein 90 (Hsp90) serves as a regulator of HIF-1α and NF-κB protein. We hypothesized that curcumin and its analogues EF31 and UBS109 would disrupt angiogenesis in pancreatic cancer (PC) through modulation of HIF-1α and NF-κB. Conditioned medium from MIA PaCa-2 or PANC-1 cells exposed to curcumin and its analogues in vitro significantly impaired angiogenesis in an egg CAM assay and blocked HUVEC tube assembly in comparison to untreated cell medium. In vivo, EF31 and UBS109 blocked the vascularization of subcutaneous matrigel plugs developed by MIA PaCa-2 in mice. Significant inhibition of VEGF, angiopoietin 1, angiopoietin 2, platelet derived growth factor, COX-2, and TGFβ secretion was observed in PC cell lines treated with UBS109, EF31 or curcumin. Treatment with UBS109, EF31 or curcumin inhibited HSP90, NF-κB, and HIF-1α transcription in PC cell lines. UBS109 and EF31 inhibited HSP90 and HIF-1α expression even when elevated due to NF-κB (p65) overexpression. Finally, we demonstrate for the first time that curcumin analogues EF31 and UBS109 induce the downregulation of HIF-1α, Hsp90, COX-2 and VEGF in tumor samples from xenograft models compared to untreated xenografts. Altogether, these results suggest that UBS109 and EF31 are potent curcumin analogues with antiangiogenic activities.